Investigation of the Core Beliefs of the Teacher Candidates through Artificial Neural Networks - Duran Volkan; Mertol Hüseyin (Sciendo, 2020)
Introduction:The research aims to investigate the relationship between pedagogical beliefs, epistemological beliefs of teacher candidates as well as their beliefs toward learning.